A typology of biconstituent hypotactic adjectival syntagms in Modern Written Arabic - Michalski, Marcin (My University, 2008)
POLSKI: Rozprawa dotyczy dwuskładnikowych (dwuwyrazowych) przymiotnikowych (w których przynajmniej jeden składnik jest przymiotnikiem) syntagm hipotaktycznych we współczesnym literackim języku arabskim. W celu przedstawienia typologii takich syntagm, będącej systematycznym opisem fragmentu składni tego języka, użyte zostały pojęcia z teorii J. Bańczerowskiego dotyczących kwalifikacji (determinacji), rządu, zgody i wyrazu. W pracy zaproponowano dziewięć wymiarów (parametrów), w które pogrupowane zostały cechy charakteryzujące syntagmy. Wymiary te tworzą przestrzeń semantyczno-syntaktyczną, w ramach której syntagmy analizowane są pod względem przynależności ich składników do kategorii części mowy, rodzaju wykładników morfologicznych, ich własności linearnych oraz własności syntaktycznych. Praca zawiera listę typów wyznaczanych przez poszczególne cechy charakteryzujące syntagmy. Syntagmy analizowane w pracy wyekscerpowane zostały z korpusu tekstów pisanych, artystycznych i prasowych. Praca zawiera rozdział poświęcony definicji przymiotnika we współczesnym literackim języku arabskim i odróżnieniu go od rzeczownika jako odrębnej części mowy.

ENGLISH: The dissertation concerns biconstituent (two-word) adjectival (having at least one adjective as their constituent) hypotactic syntagms in Modern Literary Arabic. In order to present a typology of such syntagms, intended to be a systematic description of a fragment of the syntax of this language, concepts of J. Bańczerowski’s theory have been applied concerning qualification (determination), rection (government), concord (agreement) and word. Nine dimensions (parameters) have been proposed, into which the properties of syntagms are classed. The dimensions constitute a semantic-syntactic space within which the syntagms are analyzed with respect to the category of part of speech to which their constituents belong, type of morphological indicators as well their linear and syntactic properties. The dissertation includes a list of types (categories) specified by each syntagm property. The syntagms analyzed in the study have been excerpted from a corpus of written artistic and journalistic texts. A chapter devoted to the problem of defining the adjective in Modern Literary Arabic and distinguishing it from the substantive as a separate part of speech is included.
Keywords: język arabski; modern literary Arabic; przymiotnik; adjective; typologia; typology; syntagma; syntagm; składnia; syntax